What is vallenato? a musicological approach (2004)
This work considers vallenato (the most popular genre of Colombian music) as a legitimate object of musicological analysis. In doing this it distances from exclusively contextual (explanations, very common amongst anthropologists, ethnographers, sociologists, ethnomusicologists, and cultural studies specialists. It is a characterization of this genre based on the analysis of its music and of the available contextual information about it.